Proposed Business Strategy to Develop the Ocean-Going Bunkers Business in Indonesia - Eko Frastiawan (Green Publisher Indonesia, 2022)
The global bunker fuel market is projected to reach 130,1 billion in 2027, growing at a CAGR of 3.1% from 2020 to 2027. Asia-Pacific dominates the bunker fuel market, and Singapore has been the world's pre-eminent bunker hub, with 22% of the global bunker market. It is estimated to grow at a CAGR of 3.5% from 2021 to 2030. With this growth of the bunker demand, Indonesia, which strategically lies on the world maritime trade route, should be able to take this opportunity. There are nearly 150.000 ocean-going vessels that pass through the Indonesia seas each year, and around 11.000 vessels do loading-unloading cargo in Indonesia's ports or anchorages. The business size of the ocean-going bunker in Indonesia is 1.2 Billion/year or equal to 2.2 million Metric Tons. However, only 4% (0,08 Million Metric Tons) were bunkering in Indonesian port. Mostly they were bunkering in Singapore, Port Klang, Zhoushan, and Hongkong. Estimated Indonesia’s opportunity loss from bunker transactions is 1.1 Billion/ per year, while the opportunity loss from port charges and other services is estimated at more than 1 Billion per year. This final project will use a qualitative research methodology consisting of desk research and field research through in-depth interviews of the key informants. To understand the level of competition and Indonesia's relative position in the Asia Pacific bunker market, this research uses an external analysis framework. Moreover, the internal analysis is applied to understand the current competitive advantage and list items to improve. This research recommends the Value Innovation strategy, which started with the cost-leadership focus strategy in attracting the ocean-going bunker consumer and is supported by increasing perceived customer benefits. This research suggests focusing on ocean-going ships that load and unload cargo at Indonesian ports as the target market. This research also proposes the business strategy using 7P’s marketing mix approach. It consists of raising product specifications to a global standard, eliminating VAT components, reducing shipment costs, remapping supply points, increasing awareness of the global market, developing global skilled human resources, improving the bunkering speed and quantity accuracy, and improving the reliability of infrastructure.